Adopting Bees Algorithm for Sequenced Based T-Way Test Data Generation - Kamal Z., Zamli; Mohd Hazli, Mohammed Zabil (ICIC International, 2013)
Many interaction test data generation strategies (termed t-way strategies) have been developed over the past fifteen years. Despite being very useful, those strategies have assumed sequence-less interaction among the input-values. In this paper, we studied recent works in generating test data for sequence-based t-way. We then proposed a new approach for generating sequence-based t-way, to overcome the unsupported features of the existing strategies as well as to complement the existing sequence-less t-way strategies. Using combinatorial method, our strategy adopted Bees Algorithm (BA) to generate the test data for sequence t-way. Benchmarking results show that our strategy is comparable, and produces better results in some scenarios. BA is the first bio-inspired AI strategy for sequence t-way.